Assisted oocyte activation does not overcome recurrent embryo developmental problems. Issue 5 (17th March 2023) - Cardona Barberán, A; Bonte, D; Boel, A; Thys, V; Paredis, R; Machtelinckx, F; De Sutter, P; De Croo, I; Leybaert, L; Stoop, D; Coucke, P; Vanden Meerschaut, F; et al.
Abstract: STUDY QUESTION: Can recurrent embryo developmental problems after ICSI be overcome by assisted oocyte activation (AOA)? SUMMARY ANSWER: AOA did not improve blastocyst formation in our patient cohort with recurrent embryo developmental problems after ICSI. WHAT IS KNOWN ALREADY: The use of AOA to artificially induce calcium (Ca 2+ ) rises by using Ca 2+ ionophores (mainly calcimycin and ionomycin) has been reported as very effective in overcoming fertilization failure after ICSI, especially in patients whose Ca 2+ dynamics during fertilization are deficient. However, there is only scarce and contradictory literature on the use of AOA to overcome embryo developmental problems after ICSI, and it is not clear whether abnormal Ca 2+ patterns during fertilization disturb human preimplantation embryo development. Moreover, poor embryo development after ICSI has also been linked to genetic defects in the subcortical maternal complex (SCMC) genes. STUDY DESIGN, SIZE, DURATION: This prospective cohort single-center study compared ICSI-AOA cycles and previous ICSI cycles in couples with normal fertilization rates (≥60%) but impaired embryonic development (≤15% blastocyst formation) in at least two previous ICSI cycles. In total, 42 couples with embryo developmental problems were included in this study from January 2018 to January 2021. PARTICIPANTS/MATERIALS, SETTING, METHODS: Of the 42 couples included, 17 underwent an ICSI-AOA cycle consisting of CaCl2 injection and double ionomycin exposure. Fertilization, blastocyst development, pregnancy, and live birth rates after ICSI-AOA were compared to previous ICSI cycles. In addition, the calcium pattern induced by the male patient's sperm was investigated by mouse oocyte calcium analysis. Furthermore, all 42 couples underwent genetic screening. Female patients were screened for SCMC genes ( TLE6, PADI6, NLRP2, NLRP5, NLRP7, and KHDC3L ) and male patients were screened for the sperm–oocyte-activating factor PLCZ1 . MAIN RESULTS AND THE ROLE OF CHANCE: We compared 17 AOA cycles to 44 previous ICSI cycles from the same patient cohort. After AOA, a total fertilization rate of 68.95% (131/190), a blastocyst development rate of 13.74% (18/131), a pregnancy rate of 29.41% (5/17), and a live birth rate of 23.53% (4/17) were achieved, which was not different from the previous ICSI cycles (76.25% (321/421, P -value = 0.06); 9.35% (30/321, P -value = 0.18), 25.00% (11/44, P -value = 0.75), and 15.91% (7/44, P -value = 0.48), respectively). Calcium analysis showed that patient's sperm induced calcium patterns similar to control sperm samples displaying normal embryo developmental potential. Genetic screening revealed 10 unique heterozygous variants (in NLRP2, NLRP5, NLRP7, TLE6, and PADI6 ) of uncertain significance (VUS) in 14 females. Variant NLRP5 c.623-12_623-11insTTC (p.?) was identified in two unrelated individuals and variant NLRP2 c.1572T>C (p.Asp524=) was identified in four females. Interestingly, we identified a previously reported homozygous mutation PLCZ1, c.1499C>T (p.Ser500Leu), in a male patient displaying impaired embryonic development, but not showing typical fertilization failure. LIMITATIONS, REASONS FOR CAUTION: Our strict inclusion criteria, requiring at least two ICSI cycles with impaired embryo development, reduced cycle-to-cycle variability, while the requirement of a lower blastocyst development not influenced by a poor fertilization excluded couples who otherwise would be selective cases for AOA; however, these criteria limited the sample size of this study. Targeted genetic screening might be too restricted to identify a genetic cause underlying the phenotype of poor embryo development for all patients. Moreover, causality of the identified VUS should be further determined. WIDER IMPLICATIONS OF THE FINDINGS: Strong evidence for AOA overcoming impaired embryonic development is still lacking in the literature. Thus far, only one article has reported a beneficial effect of AOA (using calcimycin) compared to previous ICSI cycles in this patient population, whilst two more recent sibling-oocyte control studies (one using calcimycin and the other ionomycin) and our research (using ionomycin) could not corroborate these findings. Although no major abnormalities have been found in children born after AOA, this technique should be reserved for couples with a clear Ca 2+ -release deficiency. Finally, genetic screening by whole-exome sequencing may reveal novel genes and variants linked to embryo developmental problems and allow the design of more personalized treatment options, such as wild-type complementary RNA or recombinant protein injection. STUDY FUNDING/COMPETING INTEREST(S): This study was supported by the Flemish Fund for Scientific Research (grant FWO.OPR.2015.0032.01 to B.H. and grant no. 1298722N to A.B.). A.C.B., D.B., A.B., V.T., R.P., F.M., I.D.C., L.L., D.S., P.D.S., P.C., and F.V.M. have nothing to disclose. B.H. reports a research grant from the Flemish Fund for Scientific Research and reports being a board member of the Belgian Society for Reproductive Medicine and the Belgian Ethical Committee on embryo research. TRIAL REGISTRATION NUMBER: NCT03354013